2021
DOI: 10.1002/jmv.27466
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies against influenza D virus in swine veterinarians in Italy in 2004

Abstract: Influenza D virus (IDV) was first isolated from a swine with respiratory disease symptoms in 2011 in the United States. Epidemiological and serological studies support the hypothesis that cattle represent the natural reservoir of IDV with periodical spillover events to other animal hosts. Little is known about the seroprevalence in humans and in specific target groups such as veterinarians in Italy. This study was designed to assess the prevalence of antibodies against two influenza D lineages (D/660 and D/OK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Overall, studies based on HI might tend to underestimate the prevalence of IDV. Similar inconsistencies have been reported in studies conducted in small ruminants and humans [ 11 , 14 ]. In contrast, a study in horses in the USA reported a strong agreement between the HI and VN seroprevalence data [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, studies based on HI might tend to underestimate the prevalence of IDV. Similar inconsistencies have been reported in studies conducted in small ruminants and humans [ 11 , 14 ]. In contrast, a study in horses in the USA reported a strong agreement between the HI and VN seroprevalence data [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
“…The presence of IDV has been reported globally, either directly or indirectly, in livestock animals [ 5 ], feral pigs and wild boars [ 6 , 7 ], camelids [ 8 ], small ruminants [ 9 , 10 , 11 ], and horses [ 12 ]. Abs specific to IDV have been also identified in humans [ 13 ], chiefly in workers with occupational exposure, i.e., veterinarians and farmers [ 14 , 15 ]. Although IDV was first isolated from pigs, cattle are presently considered as IDV’s main host and reservoir [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include the influenza D virus (IDV), a novel Orthomyxoviridae isolated in 2011 from swine with influenza-like illness ( 16 ). IDV exposure was documented in humans by serologic studies ( 17 19 ) and in several animal species ( 20 24 ), but cattle are considered its primary host ( 25 ). In the last few years, IDV detection in clinical samples has been positively associated with respiratory disease in cattle through metagenomic approaches ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, both epidemiological and serological studies support the hypothesis that cattle are the natural reservoir. To date there is no direct evidence of IDV disease in humans, but antibodies against IDV have been detected, underlining the potential ability of this virus to infect and elicit an immune response in humans and especially in people working with animals and/or exposed to cattle [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%